Case Report: Potential Applications of Using a 3D-Ring CZT SPECT for Lymphoscintigraphic Exploration of Lower Limb Edema - Besse, Hélène; Bailly, Matthieu (Frontiers in Medicine, 2022)
Lymphoscintigraphy is still considered the gold standard imaging modality for diagnosing lymphedema, due to ineffective lymphatic transport resulting in edema and skin damage. However, protocol variability and poor image resolution can make the interpretation challenging. Up to now, 99 mTc-labeled colloid lymphatic travel is monitored with dual-head cameras, but single-photon emission CT (SPECT) has proved its interest. Here, we present the case of a 59-year-old-man with bilateral asymmetric lower limb edema which was explored using dual-head and new 3D-ring cadmium -zinc-telluride (CZT) SPECT cameras, confirming bilateral lower limb lymphatic dysfunction. In line with other recently published reports, this case report promotes the use of SPECT/CT in the lymphoscintigraphic exploration of lower limb edema. The recognition of the clinicopathologic features of lower limb edema is required to prevent missed diagnoses, such as compressive disease, tumors, etc., as well as to better influence the management of patients.